HIV and its Oral Manifestations: Insights from a Case Report - Tammana Soni (Oral Sphere Journal of Dental and Health Sciences, 2025)
Background: HIV and AIDS remain one of the leading causes of global mortality, with significant socio-economic and psychological implications. Oral manifestations are essential for diagnosing HIV, as early detection of these lesions can identify the progression to AIDS. Case Presentation: A 45-year-old female patient presented with oral complaints, including gum pain, weight loss, fever, and skin lesions. Clinical examination revealed pseudomembranous candidiasis and linear gingival erythema. HIV diagnosis was confirmed through HIV antibody testing and CD4 count. The patient underwent a comprehensive clinical examination and relevant laboratory tests to assess both oral health and HIV status. HIV testing was performed using multiple assays, with a reactive result. A complete blood count (CBC) and enzyme-linked immunoassay (ELISA) test were conducted to identify HIV-related oral manifestations. The patient's CD4 count was reduced to 222 cells/mm³, indicating an impaired immune system. The observed oral lesions were consistent with HIV-related pseudomembranous candidiasis and gingivitis. After initiating Highly Active Antiretroviral Therapy (HAART), partial resolution of the lesions was observed within 20 days of treatment. Conclusion: Oral lesions, especially candidiasis, are an early indicator of HIV infection. Dentists play a vital role in detecting HIV, which enables early intervention and timely treatment. Early recognition and treatment of oral manifestations are crucial in improving the prognosis of HIV-positive patients, particularly in resource-limited settings where advanced diagnostic tools may be unavailable.